(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
This note confirms the presence of three species of Jaegers both on the Caribbean and the Pacific coasts of Colombia. In addition to an updated list of sightings for each species, the note reports on two specimens not previously recorded in the scientific literature. The presence of Catharacta skua, and possibly C. maccormicki in Colombia is also discussed.